The Psychopathy of John Berryman and Its Application to His Poetry “Not To Live” - Budi Tri Santosa (Journal of Language and Literature, 2023)
The phenomenon of psychopathic behavior that occurs in society has unconsciously inspired various forms of art, one of which is poetry. More poets write about their mental illness through indirect expression. Poetry is one of the popular ways to express it. This research aims to analyze the word or phrase in “Not To Live” to find the psychopath of the poem. The approach used in this study is a semiotic approach and uses a qualitative method. Data were collected through observation and repeated readings through heuristic and hermeneutic readings. Data analysis used descriptive qualitative analysis. The results of semiotic research in John Berryman’s poetry is that reading heuristics describes how bad the world and life are. That meaning can be seen through simile, metaphor, personification, ambiguity, and contradiction. To show the author’s personality, hermeneutic reading shows the feelings of hatred experienced by John Berryman because the world is full of hypocrites and deceit. Matrix, model, and variant in Not to Live can be seen as distorted personality due to the sorrw of his life, and proven by unrhyme matrix in his poetr. The hypnogram of the poetry is when the poet feels how real life is and how to survive. From the semiotic approach, the poem can be seen as psychopathic poetry.